2016
DOI: 10.1038/gim.2015.200
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of whole-exome sequencing and costs of the traditional diagnostic trajectory in children with intellectual disability

Abstract: Purpose: This study investigated whole-exome sequencing (WES) yield in a subset of intellectually disabled patients referred to our clinical diagnostic center and calculated the total costs of these patients' diagnostic trajectory in order to evaluate early WES implementation. Methods:We compared 17 patients' trio-WES yield with the retrospective costs of diagnostic procedures by comprehensively examining patient records and collecting resource use information for each patient, beginning with patient admittanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 37 publications
6
140
0
1
Order By: Relevance
“…3,[31][32][33][34][35][36][37][38][39][40][41][42] Seven studies presented data on the costs of WES or WGS testing pathways, [24][25][26][27][43][44][45] and eight studies presented data on clinically relevant outcome measures for these tests. 5,6,[8][9][10][46][47][48] Of the eight full economic evaluations, two were CUAs 22,23 and six were CEAs, published between 2014 and 2017 in Australia (2), the United States (1), the UK (1), the Netherlands (1), and Canada (1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[31][32][33][34][35][36][37][38][39][40][41][42] Seven studies presented data on the costs of WES or WGS testing pathways, [24][25][26][27][43][44][45] and eight studies presented data on clinically relevant outcome measures for these tests. 5,6,[8][9][10][46][47][48] Of the eight full economic evaluations, two were CUAs 22,23 and six were CEAs, published between 2014 and 2017 in Australia (2), the United States (1), the UK (1), the Netherlands (1), and Canada (1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were no regional differences: the lowest cost estimates in North America (£736; $1,060) 44 and the rest of the world (£382; $555) 32 were similar, but far less with the higher cost estimates (£3,592; $5,169 in North America, 36,38 £3,401; $4,907 in the rest of the world). 40,41 Six studies estimated the cost of WGS, four of which used data from commercial sources. 24,26,28,43 Cost estimates ranged from £1,312 ($1,906) for sequencing using the HiSeq X in Germany 26 to £17,243 ($24,810) for an unspecified platform in Canada.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, HNRNPU encodes the heterogeneous nuclear ribonucleoprotein (hnRNP) U, an abundant nucleoplasmic phosphoprotein able to bind pre-mRNA in vivo, possibly involved in pre-mRNA splicing (Roshon and Ruley 2005; Ye et al 2015). Eighteen de novo and/or truncating mutations in HNRNPU mutations have been reported in ClinVar, Decipher and in different studies (Carvill et al 2013; de Kovel et al 2016; Epi4K Consortium et al 2013; Hamdan et al 2014; Monroe et al 2016; Need et al 2012; Zhu et al 2015); however, since these mutations were reported each in separate studies and the phenotype of the patients was not described, a specific disorder related to HNRNPU mutations is not yet characterized. Although the description of these patients independently reinforced the previously proposed genotype–phenotype correlations, the dispersion of patients with point mutations in different studies and the absence of comparison with microdeletions did not permit to clearly address the clinical spectra associated with mutations in these genes, nor the possible epistatic or additive genetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have not only proven to be promising tools in studying the genetics underlying rare Mendelian disorders (12)(13)(14), but have also been shown to be valuable diagnostic tools in genetic diseases (3,8,(15)(16)(17)(18)(19). A recent review showed that although several studies on the cost-effectiveness of NGS applications have been performed, a complete and valid cost overview is currently lacking (20 ).…”
mentioning
confidence: 99%